Study of Climate Change Effect on Bird Population at Muzaffarpur Districts of Bihar - Anupama Jaiswal; Prof. S. N. Singh (International Journal of Scientific Research in Science and Technology, 2025)
Climate change has emerged as a significant threat to global biodiversity, with far-reaching consequences for bird populations. This study investigates the impact of climate change on bird population in Muzaffarpur, Bihar, India. We conducted a comprehensive survey of bird species in the region, analyzing data on population trends, habitat use, and migratory patterns. Our results indicate a significant decline in bird populations, particularly among migratory species, over the past decade. Changes in temperature and precipitation patterns as well as habitat destruction and fragmentation, were identified as primary drivers of this decline. Notably, the study reveals a shift in the migratory patterns of certain species, with some birds arriving earlier or later than usual, potentially disrupting their breeding and foraging habits. Our findings underscore the urgent need for conservation efforts to migrate the impacts of climate change on bird populations in the region. We recommend the development of climate-resilient habitats, restoration of degraded ecosystems, and implementation of adaptive management strategies to protect Muzaffarpur’s avifauna.
Keywords: Climate change; Bird populations; Conservation Biology